(untitled) (Olhares, 2019)
The present article seeks to answer whether the Book of Job, conceived around the fifth century BC, can be considered a tragedy, as well as the Greek tragedies, which were written about the same period, through a comparative analysis of this book with Prometheus Bound and the use of some concepts given by Aristotle’s Poetics for the conception of a tragedy, such as the need for prologue, epilogue, exodus and chorus. not forgetting the differences between Greek and Hebrew cultures, from which Prometheus bound and the book of Job emerged.